Flame synthesized Y2O3:Tb3+-Yb3+ phosphors as spectral convertors for solar cells - Khan, Sovann; Park, Bo-In; Han, Joon Soo; Lee, Seung Yong; Cho, So-Hye (SPRINGER, 2018)
Near-infrared (NIR) quantum cutting phosphors serve as a potential material for fabricating photovoltaic spectral convertors. In many cases, quantum cutting phosphors are obtained via a wet chemical method coupled with a post-annealing treatment-a very costly process. In this report, we used continuous flame spray pyrolysis (FSP) for fabricating Y2O3:Tb3+-Yb3+ quantum-cutting phosphors without any post-treatment. Based on characterizations by scanning electron microscopy, transmission electron microscopy, and X-ray diffraction, we found that as-synthesized Y2O3:Tb3+-Yb3+ phosphors exhibit hollow and shell-like micro-structures composed of highly crystalline and pure cubic-phase nanoparticles (< 50 nm). Photoluminescence studies of the phosphors revealed that NIR emissions appeared with the introduction of Yb to Y2O3:Tb3+. Phosphor size was successfully controlled by managing the concentration of the metal precursor solution for FSP. The Y2O3:Tb3+-Yb3+ phosphors were then embedded into transparent poly-ethylene-co-vinyl acetate (EVA) film to form a spectral convertor. The composite films of Y2O3:Tb3+-Yb3+ phosphors and poly-EVA were found to be highly transparent in the visible range (> 500 nm), making them suitable as spectral photovoltaic convertors.
Keywords: SPRAY-PYROLYSIS; NANOPARTICLES; PHOTOLUMINESCENCE